Aspirin thromboprophylaxis in joint replacement surgery. Issue 1 (24th January 2022) - Sharda, Anish V.; Fatovic, Kathy; Bauer, Kenneth A.
Abstract: Background: Aspirin is commonly used as the only pharmacologic agent for prevention of venous thromboembolism (VTE) after joint replacement surgery in the United States. Despite this, prospective studies investigating VTE events after aspirin‐only thromboprophylaxis in joint replacement surgery are lacking in the real‐world setting. Objectives: The aim of this study was to estimate the risk of VTE with aspirin‐only pharmacologic prophylaxis following joint replacement surgery. Methods: We carried out a prospective observational study of 350 low‐risk patients (no prior history of VTE and low cardiovascular risk factors) who underwent total knee and total hip arthroplasty and received only aspirin for thromboprophylaxis postoperatively. Results: The observed risk of symptomatic VTE was 1.7% (95% confidence interval, 0.9%‐3.3%) over 3 months of follow up, with only one major bleeding event and no surgical hematomas. Conclusion: The risk of VTE with aspirin monotherapy for thromboprophylaxis in joint replacement surgery in this real‐world cohort was higher than previously reported.